2006
DOI: 10.1002/sce.20154
|View full text |Cite
|
Sign up to set email alerts
|

Exploring middle school students' use of inscriptions in project-based science classrooms

Abstract: This study explores seventh graders' use of inscriptions in a teacher-designed project-based science unit. To investigate students' learning practices during the 8-month water quality unit, we collected multiple sources of data (e.g., classroom video recordings, student artifacts, and teacher interviews) and employed analytical methods that drew from a naturalistic approach. The findings showed that throughout the unit, provided with the teachers' scaffold and social, conceptual, and material resources, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
(29 reference statements)
0
12
0
4
Order By: Relevance
“…In our case study of student learning with Chemation, we found that allowing students to design a series of dynamic molecular models prompted them to think about the intermediate process in a chemical reaction, which facilitated the interpretation and reasoning of chemical phenomena at the molecular level (Chang & Quintana, 2006). Wu and Krajcik (2006) also showed that creating models provides students with opportunities to engage in thoughtful discussions on inquiry processes and scientiÞc concepts. However, having students merely view animations created by others could be similarly effective if such animations are not too complex for the students and if this is combined with activities that engage students in active learning.…”
Section: Our Predictionsmentioning
confidence: 97%
“…In our case study of student learning with Chemation, we found that allowing students to design a series of dynamic molecular models prompted them to think about the intermediate process in a chemical reaction, which facilitated the interpretation and reasoning of chemical phenomena at the molecular level (Chang & Quintana, 2006). Wu and Krajcik (2006) also showed that creating models provides students with opportunities to engage in thoughtful discussions on inquiry processes and scientiÞc concepts. However, having students merely view animations created by others could be similarly effective if such animations are not too complex for the students and if this is combined with activities that engage students in active learning.…”
Section: Our Predictionsmentioning
confidence: 97%
“…In Appendix 1, more detailed Educ Psychol Rev (2010) 22:271-296 277 information on the characteristics of the empirical descriptive studies discussed in this section (domain, measurement of scaffolding, the type of task, and the intentions and means studied as derived from Mertzman (2008), for example, examined the ways in which four elementary school teachers scaffolded the literacy of their pupils (5-8 years old) and reported the following scaffolding techniques: modeling, scolds, praise, repetition, explanations of the answer, convergent questions, focus on meaning, and focus on word recognition and phonics. As mentioned in the previous section, some other authors discerned explicitly or implicitly between the focus of scaffolding; what is scaffolded and the means or tools for scaffolding; how scaffolding is performed (e.g., Maloch 2002;Many 2002;Postholm 2006;Rodgers 2004;Silliman et al 2000;Wu and Krajcik 2006;Yelland and Masters 2007). Many (2002), for example, described what was scaffolded by two literacy teachers in third, fourth, and fifth grade (conceptual understanding and strategy use) and how it was scaffolded (e.g., modeling, supplying information, clarifying, assisting, questioning, prompting).…”
Section: Outcomes Of Descriptive Studiesmentioning
confidence: 99%
“…Some studies focused on teacher utterances or, alternatively, teacher interruptions (Mertzman 2008). Other studies focused more on the ongoing interaction and thus entailed the coding of teacher utterances in relation to student utterances (e.g., Lee 2001;Rodgers 2004;Pratt and Savoy-Levine 1998;Wu and Krajcik 2006). Lutz et al (2006) undertook detailed analyses by coding both teacher and student utterances and behavior at 30-s intervals.…”
Section: Scaffolding As An Interventionmentioning
confidence: 99%
“…These questions strive to describe the various aspects of classroom teaching and learning when implementing PBSTL, but without explicitly studying the impact (or effect or influence) of this approach on the students or teachers. The processes studied are nonetheless highly varied and it is difficult to group them together under a restricted number of dominant directions: the patterns of teacher-student discursive interactions [1]; the type of classroom discourse (scientific or common-sense) [36]; the nature of knowledge the students deal with in working on their projects in science [5] or technology [6]; students' tasks or learning processes in general ( [17,20,48]) or gender differences (comparison between boys and girls) ( [22]); the ways teachers integrate technology into their courses [37]; collaborative learning [21]; and incorporating concept mapping and other tools [41].…”
Section: Description Of the Teaching And Learning Processmentioning
confidence: 99%